Peran Edukasi dan Promosi dalam Upaya Meningkatkan Pengetahuan Masyarakat tentang Kesehatan Pikiran - Purnawinadi, I Gede; Lotulung, Christa Vike (Servitium Smart Journal, 2024)
Mental health is very crucial in achieving a comprehensive state of health, even though this has not received priority in most developing countries compared to infectious diseases, so the important role of education and promotion of mental health is something that is really needed in public health services. The speaker uses lecture and open discussion methods in health seminar sessions through questions and answers. The presenter conducted a pre-test and post-test on the participants to determine the impact of the seminar given. The main purpose of the test is to evaluate changes in understanding related to the topics that will be discussed during the seminar session. Questions are provided via the Googleform platform. Based on the evaluation results in this activity, it can be concluded that there was an increase in participants' understanding or knowledge about how to maintain a healthy mind after being given material presentation and questions and answers, most dominantly in the aspect of positive thinking (from 85.42% to 100%), laughing for a moment/humor (from 71.88% to 100%), and wheeling and meditation (from 81.25% to 100%). This proves the importance of health-related education and promotion that needs to be carried out among the public and youth communities in an effort to increase knowledge with the aim of reducing the risk or negative impact of unhealthy thoughts.